2017
DOI: 10.1007/978-1-4939-7104-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of T Lymphocyte Epitope-Based Vaccines Against Coccidioides Infection

Abstract: Coccidioidomycosis is a potentially life-threatening mycosis endemic to the Southwestern USA and some arid regions of Central and South America. A vaccine against Coccidioides infection would benefit over 30-million people who reside in or visit the endemic regions. Vaccine candidates against systemic fungal infections come in many forms. Live attenuated vaccines are derived from disease-causing pathogens and generally stimulate excellent protective immunity. Since attenuated vaccines contain living microbes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The C terminus of each antigenic peptide was flanked by a GPGPG spacer to avoid the processing of junctional epitopes, as shown in Fig. 1A (6,24). The nucleotide sequence designed to encode rCpa1 was codon optimized for translation by Escherichia coli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C terminus of each antigenic peptide was flanked by a GPGPG spacer to avoid the processing of junctional epitopes, as shown in Fig. 1A (6,24). The nucleotide sequence designed to encode rCpa1 was codon optimized for translation by Escherichia coli.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, potential antigenic epitopes can be identified in silico, since the genome sequences of both Coccidioides posadasii and Coccidioides immitis are available (33). The newly created antigen rCpa1 contains the most immunogenic fragment of Ag2/Pra, Cs-Ag, Pmp1, and five peptides derived from Pep1, Amn1, and Plb that contain human epitopes (11,18,24). These antigens were selected because they are expressed at maximum levels during different stages of the parasitic cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature T cells are divided into CD4 + T cells and CD8 + T cells according to the characteristic molecules on the cell surface. It has been found that CD4 + T lymphocytes, after being stimulated by antigen, promote the activity of natural killer cells and enhance the cytotoxic effect of T cells and play an important role in fighting coccidiosis primary infection (Hurtgen & Hung, 2017 ). CD8 + T lymphocytes play vital roles in virus immediate‐early antigens mediate protective immunity (Reddehase et al., 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…A computationally designed antigen found to be protective in animal models was first reported for the respiratory syncytial virus (RSV) F antigen in 2013 ( 79 ). Many challenging vaccine targets have since been developed rationally for HIV ( 80 82 ), hepatitis C ( 83 , 84 ), herpes ( 85 ), Zika ( 86 , 87 ), RSV ( 82 ), HPV ( 88 ), as well as for bacteria ( 82 , 89 ), fungi ( 90 ), and cancers ( 91 ). Rational vaccine design has also been utilized to improve VLP and NP vaccines by selecting a repetitive and predictive protein backbone structure for enhanced antigen presentation ( 92 ).…”
Section: Emerging Technologies In Non-viral Vaccine Developmentmentioning
confidence: 99%